PENGARUH MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN MODEL TUTORIAL PADA MATA PELAJARAN TJKT TERHADAP HASIL BELAJAR SISWA DI SMK NEGERI 6 PADANG - Novryanli, Abdul Hanif; Pratama, Ade; Kurniawan, Haris (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study was motivated by the low learning achievement of students and the minimal use of interactive learning media with tutorial models, as well as the lack of variation in the. The purpose of study was evaluate the effect of the use of interactive learning media with tutorial models achievement . The method used in this study was quantitative with an experimental type that applied .The samples in this study was determined through random sampling. Learnings outcomesi in the experimentail clasas showeid thatt moere studentis achieved hihg scorse compared to the contrle classe. The average pretest score for the experimental class was 41.14, while for the control class it was 36.57. The posttest score in the experimental class reached 85.77, while in the only 52.68. Based on these results, the Ha hypothesis is accepted and the Ho rejected. From the analysis carried out, it can be concluded that there is an effect of the use of interactive learning media achievement of class X students in TJKT lessons at SMK Negeri 6 Padang.